PENGARUH PROFITABILITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Gusnita, Lisa; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2019)
The purpose of this study is to examine further the effect of profitability, leverage and firm size on firm value. The profitability indicator, proxied by return on equity. The leverage indicator is proxied by a debt to equity ratio. And the size of the company is proxied by total assets. The population in this study were food and beverage companies listed on the Indonesia Stock Exchange in 2013-2017. The sample selection technique in this study used a purposive sampling technique with certain criteria and obtained 8 food and beverage companies that were included within a period of 5 years to obtain 40 samples. The data in this study are secondary data in the form of financial statements obtained through the Indonesia Stock Exchange and the company's official website. The results show that partially return on equity has a significant positive effect on price to book value, while the debt to equity ratio and ln.aset do not have a significant effect on price to book value. The results of the F test analysis indicate that the variable return on equity, debt to equity ratio and ln.aset together do not have a significant effect on price to book value.